Rotenone Enhances the Antifungal Properties of Staurosporine - Castro, Ana (American Society for Microbiology, 2010)
We studied staurosporine-induced cell death in the filamentous fungus Neurospora crassa. The generation of reactive oxygen species during the process appears to be an important signaling event, since addition of the antioxidant glutathione prevents the effects of staurosporine on fungal growth. Selected mutants with mutations in respiratory chain complex I are extremely sensitive to the drug, stressing the involvement of complex I in programmed cell death. Following this finding, we determined that the complex I-specific inhibitor rotenone used in combination with staurosporine results in a synergistic and specific antifungal activity, likely through a concerted action on intracellular glutathione depletion. Paradoxically, the synergistic antifungal activity of rotenone and staurosporine is observed in N. crassa complex I mutants and in Saccharomyces cerevisiae, which lacks complex I. In addition, it is not observed when other complex I inhibitors are used instead of rotenone. These results indicate that the rotenone effect is independent of complex I inhibition. The combination of rotenone and staurosporine is effective against N. crassa as well as against the common pathogens Aspergillus fumigatus and Candida albicans, pointing to its usefulness as an antifungal agent.